Jamaica : Second Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses Jamaica's Second Review Under the Extended Arrangement Under the Extended Fund Facility (EFF) and Request for Modification of Performance Criteria. Program performance is on track despite the difficult economic environment. All end-September quantitative performance criteria and structural benchmarks were met. The macroeconomic outlook and financing scenario remain broadly in line with earlier projections. The authorities are pressing ahead with the next round of reforms, including strengthening the fiscal policy framework and reforming the securities dealers sector. Based on the performance to date and the authorities' updated policy intentions and commitments, IMF staff recommends completion of the second review under the EFF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet